Ifo World Economic Survey January 2002 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2002)
World Economic Climate brightens - Economic Expectations Improved particularly in the US - Inflation in 2002 Expected to Be Lower than in 2001 - Limited Scope for Further Cuts in Short-term Interest Rates - Euro Still Regarded as Clearly Undervalued - Umemployment and Insufficient Demand Remain the Most Important Problems
Keywords: 330